Critical Analysis of Noise Pollution and Its Effect on Human Health - Tej Bahadur Karki; Raju Bhai Manandhar; Dasarath Neupane; Dipak Mahat; Padam Ban (International Journal of Educational and Life Sciences, 2024)
Noise pollution is an unseen threat. It cannot be seen, although it is present both on land and beneath the water. Any undesired or irritating sound that impacts the health and well-being of humans and other organisms is referred to as noise pollution. It is harmful to human health. According to WHO, more than 70 decibels of sound will be harmful to health. The average noise level in Kathmandu was 66.8 decibels (A), with high-traffic zones producing the most noise, followed by commercial, low-traffic, and residential zones. The main objective of this review paper is to identify the effect of noise pollution on human health. It is a reviewed article. There are different kinds of effects explored in the previous studies such as hearing loss, sleep disruption, cardiovascular disease, social handicaps, reduced productivity, bad social behavior, irritation reactions, absenteeism, and accidents. Noise pollution is a significant problem in Nepal, particularly in Kathmandu. The studies suggest that the enforcement of noise standards and No Horn Regulation can be effective in reducing noise pollution. However, more efforts are needed to monitor and enforce these regulations. Noise pollution can cause a variety of health problems, and it is essential to take measures to reduce it to protect public health.